Resolving Conflict: Enhancing Engineering Students' English Fluency through Workplace Situation - Hafizoah, Kassim; Noor Raha, Mohd Radzuan (Common Ground Publishing Pty Ltd, 2008)
Conversing in a second language particularly in English can be demanding for second language learners; they are often reluctant and embarrassed to communicate due to the fact that they are afraid they will commit grammatical inaccuracy. Concerns over accuracy often hinder studentsâ ability to speak fluently. At Universiti Malaysia Pahang (UMP) nonetheless, engineering students are frequently required to deliver project demonstrations, present research or project findings and interview people from the industry, and they can perform all these tasks very well in their native language, in this case Malay. However, when it comes to completing the tasks in English, students stumble; often projecting lack of confidence, failing to deliver the message across, and thus, disappointing the receiver. The researchers believe that the needs to, at least, improve studentsâ fluency regardless of the accuracy will help the students perform better in communicative events. Therefore, the objective of this paper is to present the researchersâ attempt at improving engineering studentsâ fluency in the English language. This has been done by exposing a group of 30 chemical engineering students to one of the most common communicative events at the workplace â conflict. They are provided with a variety of internal and external conflict scenarios and problem solving situations in which they have to resolve. Students are given opportunities to interact, deliver their opinions and resolve the issues in different speaking activities without penalizing them on the accuracy of the language.